已知:a(x*x*x*x)+b(x*x*x)+c(x*x)+dx+e=(x-2)*(x-2)*(x-2)*(x-2) A+B+C+D+E= B+D=

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 08:08:47
已知:a(x*x*x*x)+b(x*x*x)+c(x*x)+dx+e=(x-2)*(x-2)*(x-2)*(x-2)A+B+C+D+E=B+D=已知:a(x*x*x*x)+b(x*x*x)+c(x*x

已知:a(x*x*x*x)+b(x*x*x)+c(x*x)+dx+e=(x-2)*(x-2)*(x-2)*(x-2) A+B+C+D+E= B+D=
已知:a(x*x*x*x)+b(x*x*x)+c(x*x)+dx+e=(x-2)*(x-2)*(x-2)*(x-2) A+B+C+D+E= B+D=

已知:a(x*x*x*x)+b(x*x*x)+c(x*x)+dx+e=(x-2)*(x-2)*(x-2)*(x-2) A+B+C+D+E= B+D=
令x=1,A+B+C+D+E=(1-2)(1-2)(1-2)(1-2)=1
令x=-1,A-B+C-D+E=(-1-2)(-1-2)(-1-2)(-1-2)=81
所以B+D=-40